2001
DOI: 10.1161/hh0901.090301
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymorphisms in Promoter Region of ATP Binding Cassette Transporter Gene and Plasma Lipids, Severity, Progression, and Regression of Coronary Atherosclerosis and Response to Therapy

Abstract: Abstract-Identification of mutations in the ATP binding cassette transporter (ABCA1) gene in patients with Tangier disease, who exhibit reduced HDL cholesterol (HDL-C) and apolipoprotein A1 (apoA1) levels and premature coronary atherosclerosis, has led to the hypothesis that common polymorphisms in the ABCA1 gene could determine HDL-C and apoA1 levels and the risk of coronary atherosclerosis in the general population. We sequenced a 660-bp 5Ј fragment of the ABCA1 gene in 24 subjects and identified 3 novel pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 13 publications
7
48
1
1
Order By: Relevance
“…Recently, the polymorphisms in the promoter region of ABCA1, which corresponds to C()559)T in the present study and seems to be in tight linkage with G()273)C (r 2 =1, D¢-value=1), was found to be modestly, but not significantly (P=0.09), associated with the HDL-C level using LCAS subjects (Lutucuta et al 2001). The effect of the ABCA1 G()273)C polymorphism on the HDL-C level was significant, but still relatively weak (r 2 =0.0050).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Recently, the polymorphisms in the promoter region of ABCA1, which corresponds to C()559)T in the present study and seems to be in tight linkage with G()273)C (r 2 =1, D¢-value=1), was found to be modestly, but not significantly (P=0.09), associated with the HDL-C level using LCAS subjects (Lutucuta et al 2001). The effect of the ABCA1 G()273)C polymorphism on the HDL-C level was significant, but still relatively weak (r 2 =0.0050).…”
Section: Discussionsupporting
confidence: 50%
“…The effect of the ABCA1 G()273)C polymorphism on the HDL-C level was significant, but still relatively weak (r 2 =0.0050). Accordingly, the sample size (n=372) in the previous study (Lutucuta et al 2001) seems to have been too small to detect the effect of polymorphisms on the HDL-C level clearly.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We analyzed the frequency distribution of the 584C͞T SNP in a well characterized population from the LCAS (20). The LCAS and selected substudies have been published (27)(28)(29).…”
Section: El Sequence Variants Are Associated With Plasma Hdl Cholestementioning
confidence: 99%
“…A contribuição relativa de cada uma dessas fontes para o colesterol plasmático é variável e depende de fatores fisiológicos, como predisposição genética e peso corpóreo, e terapêuticos (BAYS et al, 2008 O gene que codifica a ABCA1 está localizado no cromossomo 9 e é composto por 50 éxons, 49 dos quais são codificadores da proteína (SANTAMARINA-FOJO et al, 2000). O polimorfismo de nucleotídeo único (SNP) -477C>T do ABCA1 foi associado com diferenças nas concentrações de apo AI em indivíduos tratados com fluvastatina (LUTUCUTA et al, 2001). Por outro lado, em indivíduos holandeses tratados com pravastatina não houve associação entre o SNP ABCA1 -14C>T e progressão de aterosclerose (ZWARTS et al, 2002).…”
Section: Hdl E O Transporte Reverso Do Colesterolunclassified